2017
DOI: 10.1038/ejhg.2017.133
|View full text |Cite
|
Sign up to set email alerts
|

NDUFAF4 variants are associated with Leigh syndrome and cause a specific mitochondrial complex I assembly defect

Abstract: Mitochondrial respiratory chain complex I consists of 44 different subunits and can be subgrouped into three functional modules: the Q-, the P- and the N-module. NDUFAF4 (C6ORF66) is an assembly factor of complex I that associates with assembly intermediates of the Q-module. Via exome sequencing, we identified a homozygous missense variant in a complex I-deficient patient with Leigh syndrome. Supercomplex analysis in patient fibroblasts revealed specifically altered stoichiometry. Detailed assembly analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 13 publications
2
15
0
1
Order By: Relevance
“…Given the profound disruption of CI activity observed in ECSIT-deleted macrophages ( Figure 3 ), we performed BN-PAGE followed by western blotting to examine CI and the ECSIT-containing assembly complexes. Consistent with previous reports, we found that the levels of NDUFAF1 in the ECSIT-associated subcomplexes (≈400 kDa and 700 kDa) in mitochondrial preparations were significantly decreased ( Figure 4A ), suggesting that function of the MCIA complex might be impaired ( Baertling et al, 2017 ; Guerrero-Castillo et al, 2017 ). However, in contrast to previous reports, we found that other components of CI, NDUFS3 and ND6, were substantially diminished in ECSIT KO cells and importantly, did not accumulate in detectable assembly intermediates ( Figure 4A ).…”
Section: Resultssupporting
confidence: 92%
“…Given the profound disruption of CI activity observed in ECSIT-deleted macrophages ( Figure 3 ), we performed BN-PAGE followed by western blotting to examine CI and the ECSIT-containing assembly complexes. Consistent with previous reports, we found that the levels of NDUFAF1 in the ECSIT-associated subcomplexes (≈400 kDa and 700 kDa) in mitochondrial preparations were significantly decreased ( Figure 4A ), suggesting that function of the MCIA complex might be impaired ( Baertling et al, 2017 ; Guerrero-Castillo et al, 2017 ). However, in contrast to previous reports, we found that other components of CI, NDUFS3 and ND6, were substantially diminished in ECSIT KO cells and importantly, did not accumulate in detectable assembly intermediates ( Figure 4A ).…”
Section: Resultssupporting
confidence: 92%
“…Baertling F. et al described a patient with NDUFAF4 missense variants c.194 T > C (p.Leu65Pro) displaying an early-onset with neurodevelopmental regression, hypotonia, failure to thrive and irritability [25]. Biochemical profile showed hyperlactacidemia in plasma and cerebral spinal fluid (CSF).…”
Section: Oxphos Defectsmentioning
confidence: 99%
“…Homologues of the complex are present in all domains of life and contribute to the generation of the proton motive force essential to drive energyconsuming processes (Friedrich, 2014). A dysfunction or incomplete assembly of the human complex is associated with the onset of neurodegenerative diseases such as Parkinson's syndrome (Lin and Beal 2006;Rhein et al, 2009;Baertling et al, 2017). In patients with Friedreich's ataxia, non-functional Fe/S proteins and local iron accumulation have been observed that are caused by a mutation of the gene encoding frataxin (Bidichandani and Delatycki, 1998;Isaya, 2014).…”
Section: Introductionmentioning
confidence: 99%